Successful management of a large lingual foregut duplication cyst with an ex-utero intrapartum treatment procedure - Sachiko Sakai; Yoshihiro Kubota; Masaji Tani (Elsevier, 2023)
Foregut duplication cysts are rare congenital choristomas that sometimes cause feeding and respiratory problems, depending on their size and location. Prenatal ultrasonography revealed a fetus with a large oral cystic mass and polyhydramnios. Differential diagnoses included ranula, lymphangioma, and thyroglossal duct cysts. A multidisciplinary fetal care team devised an airway management plan. We performed ex-utero intrapartum treatment (EXIT) because the origin and patency of the fetal airway could not be confirmed using fetal magnetic resonance imaging. At delivery, a lingual cyst occupied the oral cavity and protruded from the mouth. Oral intubation was performed after the aspiration of the cyst during the EXIT. On day 16, the cyst was completely excised. Histopathological examination revealed a foregut duplication cyst lined by the respiratory and gastric epithelium. Lingual foregut duplication cysts pose a risk for airway obstruction. For prenatally diagnosed cases, coordination of a multidisciplinary fetal care team and early discussions can optimize the plan for prenatal management, including the EXIT procedure.